Modern Languages Across the Curriculum - Grenfell, Michael (Taylor & Francis, 2002)
This book sets out the agenda for the future of modern language teaching in schools. It aims to look beyond the dominant methods of second language teaching to a new approach emphasising the integration of language learning within the wider curriculum. Through research and case studies from the UK, France, Spain, Italy, Germany, Belgium and Finland, the book shows how teachers and policy makers are increasingly moving towards a system where second languages are taught through other curriculum subjects, rather than alongside them. Key areas covered are: * recent trends and issues in the teaching and learning of modern foreign languages * the rationale for integrating languages across the curriculum * how cross-curricular language teaching is developing across Europe * practical materials and useful ideas for teachers and policy makers This timely book will interest all foreign language teachers, particularly those on in-service or higher level degree courses. It will also be useful reading for student teachers and educators, and policy makers, internationally.